2002
DOI: 10.1186/1476-069x-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum organochlorines and urinary porphyrin pattern in a population highly exposed to hexachlorobenzene

Abstract: BackgroundPorphyria cutanea tarda (PCT) is caused by hexachlorobenzene (HCB) in several species of laboratory mammals, but the human evidence is contradictory. In a study among adults of a population highly exposed to HCB (Flix, Catalonia, Spain), the prevalence of PCT was not increased. We aimed at analysing the association of individual urinary porphyrins with the serum concentrations of HCB and other organochlorine compounds in this highly exposed population.MethodsA cross-sectional study on total porphyrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
(35 reference statements)
1
13
0
1
Order By: Relevance
“…This finding was also supported by Vermeulen et al [19], who focused on respiratory symptoms due to occupational exposures in a contemporary general population cohort. For industries with statistically significant associations with bronchitis and/or asthma symptoms ( P < 0.10), the regression analyses were repeated based on the total occupational histories with the inclusion of time-related variables, such as duration and time since first employment.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This finding was also supported by Vermeulen et al [19], who focused on respiratory symptoms due to occupational exposures in a contemporary general population cohort. For industries with statistically significant associations with bronchitis and/or asthma symptoms ( P < 0.10), the regression analyses were repeated based on the total occupational histories with the inclusion of time-related variables, such as duration and time since first employment.…”
Section: Discussionsupporting
confidence: 80%
“…The finding for allergic skin reaction in this study was similar to Livesley et al [18], who studied symptoms among printers in the UK printing industry—itching (61%), rash (58%), and dry skin (56%). In addition, a relation was found between working in the printing industry and bronchitis-like symptoms, and although exposure to irritative solvents and paper dust may occur, it is unclear what the main risk factors are within this particular industry (Vermeulen et al [19]). Nethercott and Nosal [20] found that being an offset lithographic printing operator was related to adverse cutaneous effects, with 67% of operators having allergic contact dermatitis and 29% being caused by ultraviolet (UV) cured ink components.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary porphyrins and their homologues were analyzed by a high-performance liquid chromatography (HPLC) protocol adapted from the method described by Sunyer et al (6), and published by Alves et al (26) as described below. Chemicals used for buffered phase preparation were of analytical grade.…”
Section: Urinary Porphyrin Analysismentioning
confidence: 99%
“…These conditions have been observed after exposure to chemicals such as polychlorinated biphenyls (5), hexachlorobenzene (6), pentachlorophenol (1,7), and dioxins (8) and heavy metals such as arsenic (9,10), Hg (3), and Pb (11). They can also occur in individuals infected by some viruses such as HBV (12), HCV (12)(13)(14), and HIV (15,16) or exposed to illicit or therapeutic drugs like alcohol (17), to prolonged therapeutic use of estrogens (18) and to iron overload (13), and as adverse effects of drugs like anticonvulsants (19) and anesthetics (20).…”
Section: Introductionmentioning
confidence: 99%
“…A metodologia selecionada foi adaptada do método proposto por Sunyer et al (2002) O limite de detecção (LOD) é a menor concentração da substância em análise que o processo analítico pode diferenciar, relacionado à linha de base do detector cromatográfico (Brasil, Ministério da Saúde, 2003;Chasin, Chasin, Salvadori, 1994). Baseado neste conceito, o LOD foi calculado pela concentração que equivaleria a uma área de 500 na análise cromatográfica, conforme o programa fixado para esta análise.…”
Section: Validação Do Métodounclassified